2003
DOI: 10.1002/jpln.200390058
|View full text |Cite
|
Sign up to set email alerts
|

Soil properties, but not plant nutrients (N, P, K) interact with chemically induced resistance against powdery mildew in barley

Abstract: ± ZusammenfassungChemically induced resistance is a promising method of plant protection against diseases, which can be triggered by systemically acting chemical inducers such as BTH (benzo(1,2,3)thiadiazole-carbothioic-acid-S-methylester). BTH is commercially distributed as a 50 % formulation, called Bion . The uncertain success of Bion application in controlling infection by powdery mildew is a major obstacle in using induced resistance for plant protection in agriculture. This study aimed to investigate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Therefore, this phenomenon is often named chemically-induced resistance (cIR) when describing the systemic resistance after application of a synthetic compound. In a recent paper, we demonstrated the high variability of chemically-induced resistance using various soils and nutrient regimes in pot experiments (Wiese et al, 2003). Even if the same soil is used, variations in soil water potential may occur.…”
Section: Introductionmentioning
confidence: 93%
“…Therefore, this phenomenon is often named chemically-induced resistance (cIR) when describing the systemic resistance after application of a synthetic compound. In a recent paper, we demonstrated the high variability of chemically-induced resistance using various soils and nutrient regimes in pot experiments (Wiese et al, 2003). Even if the same soil is used, variations in soil water potential may occur.…”
Section: Introductionmentioning
confidence: 93%
“…But not all studies have found an effect of nitrogen on the efficacy of induced resistance. Wiese et al (2003) could find no effect of nitrogen on resistance induced by ASM against powdery mildew on barley in field trials. Instead, they found that resistance induced by ASM was most profoundly affected by the organic matter content of the soil, with soils containing low organic matter content exhibiting the greatest induction of resistance.…”
Section: Use Of Resistance Elicitors To Control Barley Diseases Undermentioning
confidence: 94%
“…In soils with low organic matter content and hence low microbial activity, any rhizobacteria-induced resistance would be much less, allowing ASM induced resistance to be expressed. The suggestion of Wiese et al (2003) that induction of resistance in field-grown barley by the soil microbial population might affect the ability of the plant to respond to ASM is interesting in the light of recent work on barley responding to the elicitor combination ASM + BABA + cis-jasmone (Walters et al 2011b). Here, the authors found that if plants were already infected with R. commune, their ability to respond to the elicitor combination was significantly compromised.…”
Section: Use Of Resistance Elicitors To Control Barley Diseases Undermentioning
confidence: 97%
“…Instead, they found that resistance induced by ASM was most profoundly affected by the organic matter content of the soil, with soils containing low organic matter content exhibiting the greatest induction of resistance. The authors suggested that high microbial activity in soils with high organic matter content may have led to a high degree of resistance, possibly induced by rhizobacteria and which could not be further enhanced by ASM (Wiese et al 2003). In soils with low organic matter content and hence low microbial activity, any rhizobacteria-induced resistance would be much less, allowing ASM-induced resistance to be expressed.…”
mentioning
confidence: 99%
“…However, not all studies have found an effect of nitrogen on the efficacy of induced resistance. Wiese et al (2003) could find no effect of nitrogen on resistance induced by ASM against powdery mildew on barley in field trials. Instead, they found that resistance induced by ASM was most profoundly affected by the organic matter content of the soil, with soils containing low organic matter content exhibiting the greatest induction of resistance.…”
mentioning
confidence: 99%